Intergenerational mobility in the 19th century: Micro-level evidence from the city of Zurich - Giacomin Favre; Joël Floris; Ulrich Woitek (University of Zurich, Department of Economics, 2018)
We analyze social mobility of decennial citizenry cohorts of Zurich born between 1780 and 1870. We categorize individuals according to their occupations and use different measures to show the level, change, and components of intergenerational mobility. Mobility was imperfect and weakly decreasing over time. Both level and change are driven by intergenerational persistence of occupations with a low socioeconomic position and low transition between low and high socioeconomic position.
Keywords: J62; N33; N34; 330; Social mobility; occupational mobility; 19th century; Switzerland